MANAJEMEN KONJUNKTIF SUMBER DAYA PERMUKAAN DAN SUMBER DAYA AIR - ARISMAWAN ARISMAWAN (Portal: Jurnal Teknik Sipil, 2014)
Management of the conjunctive use of surface and groundwater resources is essential, as the combination of these two water resources result in huge advantages for the quality of water, irrigation and economic benefit for the farmers and country. The advantages of proper conjunctive management not only secure the availability of water in the whole year but also can be utilised to provide safer potable water for humans. However, it is not an easy thing to manage both resources since they face several challenges and causes conflict because the nature of surface and groundwater resources is very far different. Furthermore, in order can be used as a safe drinking water then the water resources have to be managed free from contaminants and pollutants. In term of economy, better irrigation system could increase the quality and the quantity of crop’s harvest, make the soil more fertile and productive, and elevate horticulture and viticulture industries. All these things are very essential not only to increase better lives of farmers but also lead to many economic gains to the nation.